Psychometric properties of Chinese translated body compassion scale (BCS) among Hong Kong adolescents - Ming Yu Claudia Wong; Pak Kwong Chung; Ka Man Leung (Elsevier, 2022)
Background/Objectives: Adolescence is at a transition stage of developmental psychology, and they must go through their psychosocial and identity crisis, which affect their self-concept. According to the structure of self-concept, physical is considered as one of the elements affecting a person's evolvement of self, which can be called as physical self-esteem. In regards to the equilibrium mental benefits of self-compassion, the concept of body compassion was focused. Together with the lack of body-part related research being further investigated among non-western countries, this research aimed at translating the Body Compassion Scale (BCS) to Chinese and examining the reliability and validity of the Chinese translated BCS among Hong Kong adolescents. Methods: The reliability of the translated BCS was examined by the test-retest reliability test as well as the Cronbach's alpha value for the internal consistency. The confirmatory factor analysis (CFA) was adopted to investigate the construct validity, and Pearson's correlation was used to examine the convergent validity with other related scales. Results: The Chinese translated BCS (Pilot Study: n = 220; Main Study: n = 1047) showed adequate psychometric properties results. It had a satisfying internal consistency and test-retest reliability. It showed an adequate goodness of fit results in CFA, with X2(465.64)/227 = 2.05,p < 0.001, CFI = 0.916, TLI = 0.906,SRMR = 0.071,RMSEA = 0.069 [90% CI = 0.06 to 0.078]. Additionally, the measurement invariance model suggested that the factor loadings and mean differences of the translated BCS were invariant across early and older adolescents. Conclusion: The Chinese translated BCS is considered as valid and reliable in examining Hong Kong adolescents' body compassion.